Step 1: Multiply the coefficients. 2 * 5 * 2 = 20
Step 2: Simplify the exponents. 10^6 * 10^-2 = 10^4
Step 3: Do not change the exponent.
Step 4: 20 x 10^4 = 2 x 10^5
Final Answer: 2 x 10^5
Simplify this expression and put your final answer in Scientific Notation: (2
(5 * 10 ^ 6) * (2 * 10 ^-2) (4 points)
Step 1: ___ the coefficients.
Step 2: ___ to simplify the exponents.
Step 3: ___ to change the exponet for Scientific Notation.
Step 4: ___ is the final answer
Step 1: Add,Subtract,Multiply,Divide
Step 2: Add,Subtract,Multiply,Divide
Step 3: Add to the exponent, Subtract from the exponent, Do not change the exponent
Step 4: 2.5 x 10^4 | 7.0 x 10^4 | 1 x 10^5 | 10 x 10^4 | 1 x 10^3
3 answers
Completely wrong
I apologize for the mistake. Let's try solving the expression again.
Step 1: Multiply the coefficients. 2 * 5 = 10
Step 2: Add the exponents. 10^6 * 10^-2 = 10^(6 + (-2)) = 10^4
Step 3: Do not change the exponent.
Step 4: 10 x 10^4 = 1 x 10^5
Final Answer: 1 x 10^5
Step 1: Multiply the coefficients. 2 * 5 = 10
Step 2: Add the exponents. 10^6 * 10^-2 = 10^(6 + (-2)) = 10^4
Step 3: Do not change the exponent.
Step 4: 10 x 10^4 = 1 x 10^5
Final Answer: 1 x 10^5